2018
DOI: 10.1002/etc.4139
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro and in vivo effects of chlorpyrifos oxon in the outbred CD‐1 mouse (Mus musculus) and great plains toad (Anaxyrus cognatus)

Abstract: We compared biochemical, functional, and behavioral responses to the organophosphorus anticholinesterase chlorpyrifos oxon (CPO) in mice (Mus musculus, CD-1) and toads (Anaxyrus cognatus, Great Plains toad). Toads were substantially less sensitive to acute lethality of CPO based on the maximum tolerated (nonlethal) dose (toads, 77 mg/kg; mice, 5.9 mg/kg). Sublethal exposures led to classical signs of toxicity (increased involuntary movements, autonomic secretions) in mice but hypoactivity in toads. Motor perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Brain tissues were homogenized 1:10 (w/v) in phosphate buffered saline (100 mM phosphate containing 1.54 M NaCl, pH 7.4) for measurements of AChE, BChE, MAGL, and FAAH activity. AChE, BChE, and MAGL were measured using a photometric assay (Anderson et al, 2018) based on the method of Ellman et al (1961). A cocktail containing substrate (1 mM acetylthiocholine, 1 mM butyrylthiocholine, or 0.1 mM 2-arachidonoyl thioglycerol) and 0.1 mM 5,5 0 -dithio-bis-(2-nitrobenzoic acid) in Tris-E (10 mM Tris-HCl containing 1 mM EDTA, pH 7.2) was added to start the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Brain tissues were homogenized 1:10 (w/v) in phosphate buffered saline (100 mM phosphate containing 1.54 M NaCl, pH 7.4) for measurements of AChE, BChE, MAGL, and FAAH activity. AChE, BChE, and MAGL were measured using a photometric assay (Anderson et al, 2018) based on the method of Ellman et al (1961). A cocktail containing substrate (1 mM acetylthiocholine, 1 mM butyrylthiocholine, or 0.1 mM 2-arachidonoyl thioglycerol) and 0.1 mM 5,5 0 -dithio-bis-(2-nitrobenzoic acid) in Tris-E (10 mM Tris-HCl containing 1 mM EDTA, pH 7.2) was added to start the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Also, a tolerance level of 100 ppb is defined for chlorpyrifos residues, per se, in or on food commodities (Regulations, 2020). It was revealed that consumption of the residues of this chemical can result in diarrhea, frequent urination, abnormal sweating, salivation, lacrimation, genotoxicity, neurochemical changes, neurobehavioral disorder, and abnormal birth outcomes (Anderson et al, 2018;Farkhondeh et al, 2020;Foong et al, 2020). Therefore, its indoor application was banned by EPA since the early 21st century.…”
Section: Pesticide Preparationmentioning
confidence: 99%